2018
DOI: 10.13181/mji.v27i4.2910
|View full text |Cite
|
Sign up to set email alerts
|

Total serum IgE levels among adults patients with intermittent and persistent allergic asthmas

Abstract: Background: Obesity with knee osteoarthritis (OA) is related to chronic pain causing physical inactivity that leads to decreased cardiorespiratory endurance and quality of life. Aquatic and land-based exercises are effective in improving physical activity. The aim of this study is to compare between aquatic and land-based exercise to improve cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis.Methods: A single-blind, randomized, controlled trial was conducted on thirty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…These inflammatory mediators promote further constriction of airways by causing excessive mucus secretion (31). The results of the present study are in agreement with previous results; significantly elevated levels of IgE antibodies were observed amongst the asthmatic patients compared with the healthy individuals (3,32,33). The results of the present study showed a significant association between the rs20541 SNP of IL-13 and total IgE serum levels, in which pure minor alleles were significantly associated with reduced IgE serum levels (~5x lower) compared with major alleles in asthmatic subjects.…”
Section: Discussionsupporting
confidence: 93%
“…These inflammatory mediators promote further constriction of airways by causing excessive mucus secretion (31). The results of the present study are in agreement with previous results; significantly elevated levels of IgE antibodies were observed amongst the asthmatic patients compared with the healthy individuals (3,32,33). The results of the present study showed a significant association between the rs20541 SNP of IL-13 and total IgE serum levels, in which pure minor alleles were significantly associated with reduced IgE serum levels (~5x lower) compared with major alleles in asthmatic subjects.…”
Section: Discussionsupporting
confidence: 93%
“…The average IgE concentration in HBRA was 430.72 IU/ml and in NBRA it was 283.59 IU/ml. It was known that the average levels of IgE in the resident of both regions are above normal value (1.5-144 kU/l), according to Rengganis et al [21]. Analysis of IgE with Mann whitney U test showed higher average values in exposed persons compared to controls and statistically significant (P=0.0482).…”
Section: Resultsmentioning
confidence: 90%
“…The IgE concentration in males was significantly higher than females in both populations (P<0.05). The study on IgE concentration in Western European countries showed the total reference range of IgE as normal in young adults is 95 th percentile of the total IgE reference value (148 IU/ml in women, 169 IU/ml in men) [21]. It was also noted that a high concentration of IgE in male is associated with smoking habits [23].…”
Section: Resultsmentioning
confidence: 99%
“…The tools for assessing asthma severity are not consistent among studies and different guidelines recommend using different methods to identify asthma severity e.g., the Global Initiative for Asthma (GINA) criteria classifies asthma as mild, moderate, and severe while National Institute of Health in USA (NIH) classifies it as intermittent and persistent. 22 Most patients with asthma have a mild or moderate disease and data on the prevalence of severe asthma is sparse but reports indicate between 5 and 10% of the asthmatic populations to have had severe disease. 23 In this study, the method used for classifying asthma severity incorporated patient's symptoms into pulmonary function test but the main parameter was the results of FEV1 which made the results of pulmonary function tests statistically significantly different among the different asthma severity groups.…”
Section: Discussionmentioning
confidence: 99%